Synthesis and Aggregation Behaviour of Thermo-Sensitive Copolymer of N-Isopropylacrylamide and Sodium Vinylsulphonate - Tan*, Yebang; Zhang, Hong; Liu, Fawen; Wang, Minggang (Asian Journal of Chemistry, 2014)
A series of thermo-sensitive copolymers of poly(N-isopropylacrylamide-co-sodium vinyl sulphonate) (PNIPAAm-co-SVS) were synthesized by radical copolymerization of N-isopropylacrylamide and sodium vinyl sulphonate in water using 2,2'-azobis (2-methylpropionamide) dihydrochloride (V-50) as the initiator. These copolymers exhibit different lower critical solution temperatures due to their distinct monomer ratios. The salt and pH-tuned phase separation behaviorus of the copolymers were studied by UV-visible spectrophotometry. The results show that the lower critical solution temperatures (LCST) of the copolymers decreased sharply with the increase of NaCl concentration or the decrease of pH value. Aggregation behaviour of the copolymers in aqueous solution as a function of copolymer composition, added salt and pH value were also studied by dynamic laser light scattering.